Identification of SARS-CoV-2 Mpro inhibitors containing P1’ 4-fluorobenzothiazole moiety highly active against SARS-CoV-2 - Higashi-Kuwata, Nobuyo; Tsuji, Kohei; Hayashi, Hironori; Bulut, Haydar; Kiso, Maki; Imai, Masaki; Ogata-Aoki, Hiromi; Ishii, Takahiro; Kobayakawa, Takuya; Nakano, Kenta; Takamune, Nobutoki; Kishimoto, Naoki; et al. (Nature communications, 2023)
COVID-19 caused by SARS-CoV-2 has continually been serious threat to public health worldwide. While a few anti-SARS-CoV-2 therapeutics are currently available, their antiviral potency is not sufficient. Here, we identify two orally available 4-fluoro-benzothiazole-containing small molecules, TKB245 and TKB248, which specifically inhibit the enzymatic activity of main protease (M pro ) of SARS-CoV-2 and significantly more potently block the infectivity and replication of various SARS-CoV-2 strains than nirmatrelvir, molnupiravir, and ensitrelvir in cell-based assays employing various target cells. Both compounds also block the replication of Delta and Omicron variants in human-ACE2-knocked-in mice. Native mass spectrometric analysis reveals that both compounds bind to dimer M pro , apparently promoting M pro dimerization. X-ray crystallographic analysis shows that both compounds bind to M pro ’s active-site cavity, forming a covalent bond with the catalytic amino acid Cys-145 with the 4-fluorine of the benzothiazole moiety pointed to solvent. The data suggest that TKB245 and TKB248 might serve as potential therapeutics for COVID-19 and shed light upon further optimization to develop more potent and safer anti-SARS-CoV-2 therapeutics. Effective antivirals are critical for combatting SARS-CoV-2 infections. Here, the authors develop two orally available small molecules, which specifically inhibit the activity of the SARS-CoV-2 main protease and potently block the infectivity and replication of various SARS-CoV-2 strains in cells and mice.